The Major Catalase Gene (katA) of Pseudomonas aeruginosa PA14 Is under both Positive and Negative Control of the Global Transactivator OxyR in Response to Hydrogen Peroxide - Heo, Yun-Jeong (American Society for Microbiology (ASM), 2010)
The adaptive response to hydrogen peroxide (H(2)O(2)) in Pseudomonas aeruginosa involves the major catalase, KatA, and OxyR. However, neither the molecular basis nor the relationship between the aforementioned proteins has been established. Here, we demonstrate that the transcriptional activation of the katA promoter (katAp) in response to H(2)O(2) was abrogated in the P. aeruginosa PA14 oxyR null mutant. Promoter deletion analyses revealed that H(2)O(2)-mediated induction was dependent on a region of DNA −76 to −36 upstream of the H(2)O(2)-responsive transcriptional start site. This region harbored the potential operator sites (OxyR-responsive element [ORE]) of the Escherichia coli OxyR binding consensus. Deletion of the entire ORE not only abolished H(2)O(2)-mediated induction but also elevated the basal transcription, suggesting the involvement of OxyR and the ORE in both transcriptional activation and repression. OxyR bound to the ORE both in vivo and in vitro, demonstrating that OxyR directly regulates the katAp. Three distinct mobility species of oxidized OxyR were observed in response to 1 mM H(2)O(2), as assessed by free thiol trapping using 4-acetamido-4′-maleimidylstilbene-2,2′-disulfonic acid. These oxidized species were not observed for the double mutants with mutations in the conserved cysteine (Cys) residues (C199 and C208). The uninduced transcription of katAp was elevated in an oxyR mutant with a mutation of Cys to serine at 199 (C199S) and even higher in the oxyR mutant with a mutation of Cys to alanine at 199 (C199A) but not in oxyR mutants with mutations in C208 (C208S and C208A). In both the C199S and the C208S mutant, however, katAp transcription was still induced by H(2)O(2) treatment, unlike in the oxyR null mutant and the C199A mutant. The double mutants with mutations in both Cys residues (C199S C208S and C199A C208S) did not differ from the C199A mutant. Taken together, our results suggest that P. aeruginosa OxyR is a bona fide transcriptional regulator of the katA gene, sensing H(2)O(2) based on the conserved Cys residues, involving more than one oxidation as well as activation state in vivo.